Procesos de exclusión social hacia las identidades trans femeninas - Román Chimbay, José David; Quinteros Zambrano, Gustavo Andrés (Machala: Universidad Técnica de Machala, 2022)
The present research work investigates the processes of social exclusion towards trans feminine identities. Therefore, to support its importance, scientific texts are presented that reflect statistical data on the vulnerability of rights towards these femininities, culminating with research that indicates the feelings that these processes of exclusion have caused in them. The approach of this study is qualitative in nature, in which observation instruments and in-depth interviews were used, in addition to MAXQDA software for the analysis of the results. Now, with respect to the sampling, it is of homogeneous and snowball type considering six trans identities as a sample for this research. In this sense, through the analysis of the observations and interviews conducted, it is evident that in the family environment there is no acceptance, support or acceptance by the parents. Within the educational environment, rejection and exclusion are evidenced by binary thought structures of both teachers and students. Then, within the work environment, it is evident that despite the existing laws on equality for all people, this is not carried out effectively, because most of the time trans femininity goes through a lot of discrimination when accessing a job. Finally, by way of conclusion, it was evidenced that the six trans femininities who participated in the study have suffered exclusion by society, whose process has started from their own families, then in educational centers, to later be excluded from the labor field. These exclusion processes make the quality of life of these femininities low because they lack economic resourcesand adequate social means for their personal improvement. As for recommendations, in the family environment it is recommended to work hard on acceptance, improve communication and above all understanding of these diversities. With regard to education, it is recommended to carry out inclusion activities for higher education students so that they become inclusive individuals. Finally, in the labor field, it is recommended that the Ministry of Labor and/or organizations that defend human rights can carry out training on inclusion in different public or private establishments. In this sense, the psychoanalytic approach in people with diverse sexual orientations proposes not to be patriarchal, heteronormative-biological and colonial, since these factors cause discomfort in the individual. On the contrary, this treatment should be a post-patriarchal, post-heteronormative and post-colonial practice, leaving prejudices behind so that in this way, quality care can be given to patients with diverse gender identities.
El presente trabajo de investigación indaga los procesos de exclusión social hacia las identidades trans femeninas. Por consiguiente, para sustentar su importancia, se presentan textos científicos que reflejan datos estadísticos sobre la vulnerabilidad de derechos hacia estas feminidades, culminando con investigaciones que indican los sentimientos que estos procesos de exclusión han provocado en ellas. El enfoque de este estudio es de carácter cualitativo, en el que, se utilizaron instrumentos de observación y la entrevista profunda, además, del software MAXQDA para el análisis de los resultados. Ahora, con respecto al muestreo, es de tipo homogénea y en bola de nieve, considerando a seis identidades trans como muestra para esta investigación. En este sentido, mediante el análisis de las observaciones y las entrevistas realizadas se evidencia que, en el ámbito familiar no existe acogimiento, apoyo, ni aceptación por parte de los padres. Dentro del ámbito educativo, se evidencian rechazos y exclusiones por estructuras de pensamientos binarios tanto de los docentes como de los estudiantes. Luego, dentro del ámbito laboral se evidencia que pese a las leyes existentes sobre igualdad para todas las personas, esta no se lleva a cabo de manera efectiva, debido que la mayoría de veces las feminidades trans pasan por mucha discriminación cuando acceden a un trabajo. Finalmente, a manera de conclusión, se evidenció que las seis feminidades trans que participaron en el estudio han sufrido exclusión por parte de la sociedad, cuyo proceso ha iniciado desde sus propias familias, luego en centros educativos, a posteriori ser excluidas del campo laboral. Estos procesos de exclusión hacen que la calidad de vida de estas feminidades sea baja porque carecen de recursos económicos y medios sociales adecuados para su superación personal. En cuanto a las recomendaciones, en el ámbito familiar se recomienda trabajar mucho en la aceptación, mejorar la comunicación y sobre todo el entendimiento hacia estas diversidades. Con relación al ámbito educativo es recomendable realizar actividades de inclusión a los estudiantes de educación superior para que sean individuos inclusivos. Finalmente, en el ámbito laboral se recomienda que el ministerio de trabajo y/o las organizaciones que defienden los derechos humanos puedan realizar capacitaciones sobre inclusión en los diferentes establecimientos públicos o privados. En este sentido, el abordaje psicoanalítico en personas con orientaciones sexuales diversas propone, no ser patriarcal, heteronormativo-biologicista y colonial, ya que estos factores causan malestar en el individuo. Al contrario, este tratamiento debe ser una práctica pospatriarcal, posheteronormativo y poscolonial, dejando atrás los prejuicios para que, de esta manera, se pueda dar una atención de calidad a los pacientes con identidades de género diversas.
Keywords: EXCLUSION SOCIAL; TRANSGENERO; FEMINIDAD